PERCEPTION OF THE HIJAB USAGE AS SELF-CONTROL AGAINST THE KOREAN WAVE (International Conference on Social and Islamic Studies, 2022)
The Korean wave is a cultural product as a result of globalization that is favored by the world community, not least in Indonesia. The Korean wave comes with a variety of interesting cultural products, one of which is the power of dress. The problem then arises due to the trend of Korean clothing which is considered to be more modern and obscures the nuances of dressing according to the norm. Moreover, the use of hijab among Muslim youth. The writing of this paper uses a type of research, namely library research with a qualitative method. This article aims to examine the perception of the use of hijab as a form of self-control against the Korean wave. Based on data from relevant books, journals and literature, it was found that apart from being used as a form of obligation as a Muslim woman, the hijab can also be self-control for the wearer.